A model of metacognition for bushfire fighters. Issue 3 (August 2016) - Frye, Lisa; Wearing, Alexander
Abstract Large-scale bushfires are complex ormacrocognitive decision environments (Klein et al.). They involve many people, such as incident management teams, firefighting crews, and resident communities. Those people can also be geographically dispersed. This means that they need to coordinate their bushfire response efforts and manage multiple, often competing, cognitive demands. To do this, bushfire responders need to usemetacognitive skills to regulate their thinking, particularly under stressful high cognitive load conditions. We explored these types of issues with career and volunteer bushfire fighters (Frye and Wearing in J Cogn Technol 16(2): 33–44, 2011). We found that rule-based procedures can sometimes reduce errors, and increase safety, because they reduce cognitive load (e.g., 'you just do it'). However, fixation on other rules and procedures can increase errors, and erode safety, because people fail to adapt to the current situation (e.g., 'you really need to think about that'). In this paper we use a model ofmetacognition to describe how experts regulate their thinking and thus avoid errors associated with cognitive overload (such as tunnel vision and goal fixation) during large-scale bushfires. The implications for bushfire training and procedures are discussed.